dampak teknologi terhadap geopolitik di era digital global - Ilhan, Muhammad (Maliki Interdisciplinary Journal, 2025)
Globalization and the advancement of digital technology bring new challenges and opportunities to the global geopolitical order. This article aims to analyze the role of technology in reshaping the global power structure, as well as its impact on state sovereignty, cybersecurity, and diplomatic relations between countries. Using a qualitative descriptive approach based on literature studies, this study examines the dominance of digital infrastructure, cyber conflict, and inequality in access to technology between developed and developing countries. This article discusses various strategic aspects, such as strengthening digital defense, forming technology alliances, and the importance of global regulation and international collaboration. The results of the analysis show that technological mastery is a new indicator of state power and a modern diplomatic tool that is influential in the geopolitical arena. In addition, cross-country collaboration, empowerment of the younger generation, and national innovation are the keys to maintaining digital sovereignty and strengthening the country’s position in the global era. This study recommends that the government and stakeholders formulate adaptive and participatory policies in facing digital geopolitical challenges, in order to create a safe, fair, and sustainable global technology ecosystem.